Katabaza dandysa. O "Tajemnicach Paryża" = Catabasis of a Dandy: "The Mysteries of Paris" - Powązka, Elżbieta; Solecka, Teresa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, the authors explore the main issues raised in the Western studies of E. Sue`s TheMysteries of Paris. They outline the origins of the book, which has contributed to the popularizationof the serial novels andt hey present the characteristics of this type of literature. Thanks to thedetailed descriptions of Paris, the novel has become one of the most famous nineteenth-centuryportraits of this most fascinating city in Europe.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); literatura francuska - historia - 19 w.; powieść francuska - 19 w.